The wage gap between male and female agricultural workers: Analysis and implications for gender and development policy - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2018)
The gender gap is a key policy issue across the economic sectors, including agriculture. While the Philippines has - in general - made considerable progress in addressing the gender gap, gender gap in average wages remains a key concern in the case of agriculture. Such wage gap can be attributed to differences in activity composition by sex of worker and differences in daily pay for the same activity. This study performs, for the first time, a decomposition of the average wage gap into these two sources, using official data, supplemented by data from an ongoing survey of agricultural workers. The study finds that activity composition is only a minor contributor to the gender wage gap; most of the gap rather arises from differences in pay for the same activity. Further research is recommended to confirm this finding. The study discusses some policy implications, related to promoting gender equality in daily pay in agriculture.
Keywords: 330; gender gap; gender and development; agricultural labor market; wage gap decomposition